1976
DOI: 10.1002/jso.2930080610
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CEA, tumor CEA, and tumor histology

Abstract: Carcinoembryonic antigen (CEA) has been thought to be a diagnostic and prognostic indicator of colorectal cancer. Initial descriptions of CEA as a tumor specific antigen suggests a relationship between tumor CEA and circulating plasma CEA. To define the relationship between CEA and colorectal carcinoma, we have studied the CEA concentration of preoperative plasma, tumor tissue, and normal bowel distant from tumor in 35 patients who had clinically curative resections. Tumor histology was evaluated for Dukes cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, early findings and our data revealed that elevated serum levels of CEA do not necessarily connote elevated tumor tissue levels of CEA [32, 33]. Elevated serum CEA levels in advanced CRC may be due to increased access of CRC cells to bloodstream and/or related to increased tumor mass in which CEA −/lo cells can differentiate into CEA + cells.…”
Section: Discussionmentioning
confidence: 58%
“…However, early findings and our data revealed that elevated serum levels of CEA do not necessarily connote elevated tumor tissue levels of CEA [32, 33]. Elevated serum CEA levels in advanced CRC may be due to increased access of CRC cells to bloodstream and/or related to increased tumor mass in which CEA −/lo cells can differentiate into CEA + cells.…”
Section: Discussionmentioning
confidence: 58%